Experimental investigations on drag-reduction characteristics of bionic surface with water-trapping microstructures of fish scales - Wu, Liyan; Jiao, Zhibin; Song, Yuqiu; Liu, Cuihong; Wang, Huan; Yan, Yuying (Nature Publishing Group, 2018)
Biological surfaces with unique wettability in nature have provided an enormous innovation for scientists and engineers. More specifically, materials possessing various wetting properties have drawn considerable attention owing to their promising application prospects. Recently, great efforts have been concentrated on the researches on wetting-induced drag-reduction materials inspired by biology because of their ability to save energy. In this work, the drag-reduction characteristics of the bionic surface with delicate water-trapping microstructures of fish Ctenopharyngodon idellus scales were explored by experimental method. Firstly, the resistance of smooth surface and bionic surface experimental sample at different speeds was carefully tested through the testing system for operation resistance. Then, the contact angle (CA) of fish scale surface was measured by means of the contact angle measuring instrument. It was discovered that the bionic surface created a rewarding drag-reduction effect at a low speed, and the drag-reduction rate significantly displayed a downward trend with the increase in flow speed. Thus, when the rate was 0.66 m/s, the drag-reduction effect was at the optimum level, and the maximum drag reduction rate was 2.805%, which was in concordance with the simulated one. Furthermore, a contact angle (CA) of 11.5° appeared on the fish scale surface, exhibiting fine hydrophilic property. It further manifested the spreading-wetting phenomenon and the higher surface energy for the area of apical of fish scales, which played an important role in drag-reduction performance. This work will have a great potential in the engineering and transportation field.